In vitro propagation and acclimatization of Lippia rotundifolia, an endemic species of Brazilian Campos Rupestres (Revista Ciência Agronômica, 2015)
The importance in folk medicine, combined to threats in their environment, becomes necessary to carry outstudies involving large-scale propagation of Lippia genus. Although the tissue culture propagation is widely disseminated formedicinal plants, for L. rotundifolia any article was published yet. The present study aimed to establish an efficient protocol formicropropagation of L. rotundifolia. Nodal segments, taken from plants collected in the Espinhaço Range, were disinfected, andcultures were initiated on MS medium with PVPP (1 g L- 1), sucrose (3%) and agar (0.7%). The culture were maintained in agrowth room at controlled conditions. Disinfestation procedures and the supply of PVPP on culture media resulted in both reducedcontamination and phenol oxidation rates, with more than 90% of viable cultures. In the multiplication phase were tried differentBAP and NAA combinations supplied to the MS medium. The treatment that resulted in highest multiplication rates was 0.33ȝM BAP. The effects of NAA were evaluated for in vitro rooting. At 0.44 ȝM, rooting was 70% higher than that observed in thecontrol. The acclimatization was held in trays with substrate, coated with translucent plastic and kept under shade. The plantletswere transferred to the greenhouse after 15 days and transplanted to plant beds after 30 days. The acclimatized plantletsbloomed one year after the transference to field conditions, showing that the in vitro culture did not affect the vegetative andreproductive development, which confirms the potential of micropropagation to reduce the extinction risk of L. rotundifolia.